Pengetahuan Pasien Terhadap Adverse Drug Reactions (ADRs) Penggunaan Obat Antibiotik Beta-Laktam di RSUD Bendan Tahun 2024 - Ghiska Ma’alia Yusuf; Musa Fitri Fatkhiya (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Knowledge is the result of the process of understanding and recognizing something obtained through sensing an object. Beta-lactam antibiotics are a type of broad-spectrum antibiotic commonly used to treat bacterial infections, but their use still has the potential to cause side effects in the form of Adverse Drug Reactions (ADRs). This study aims to assess the level of patient knowledge regarding ADRs due to the use of beta-lactam antibiotics at Bendan Pekalongan Regional Hospital in 2024. This study used a prospective correlation design with a non-experimental approach. A total of 29 outpatients taking beta-lactam antibiotics were sampled, selected using a purposive sampling technique. Data were collected through questionnaires, medical records, and analyzed descriptively using Microsoft Excel. The results showed that 41% of respondents had low knowledge regarding ADRs, 28% had sufficient knowledge, and 31% had good knowledge. These findings indicate the need for more intensive education regarding the risks of ADRs in order to improve the safety of antibiotic use.